Traceability of optical frequency to SI second via UTC(NIM) - Wang, Yuzhuo; Lin, Yige; Gao, Yuan; Zhang, Aimin (Frontiers in Physics, 2022)
Absolute frequency measurement of an optical clock is a milestone towards the redefinition of second in the International System of Units. This work summarizes briefly the measurement of frequency ratio between an optical clock and the second, applying the frequency comparison link from UTC(NIM) to International Atomic Time. Some strategies and suggestions are proposed to reduce the uncertainty introduced by the measurement system and dead time, which guided the frequency measurement of three optical clocks at 10−16 level in the past 3 years.